VCO (Virgine Coconut Oil) Preparation by Enzymatic Method Using Crude Papain - Winarti, Sri; Jariyah, Jariyah; Purnomo, Yudi (Fakultas Teknologi Pertanian Universitas Brawijaya, 2007)
Virgin Coconut Oil (VCO) is the pure oil from fresh coconut fruits, made with low temperature/without heating. This oil contains lauric acid of 48%, a type of MCFA (Medium Saturated Chain Fatty Acid). This fatty acid is easily absorbed in metabolism and produces energy, but does not induce cholesterol rise. The purpose of crude papain addition is to increase the hydrolysis rate of protein stabilized emulsion in coconut emulsion. The purpose of this research is to find out the optimum crude papain concentration and incubation temperature in VCO preparation. Experimental design employed in this research is Randomized Complete Design with 2 factors; i.e. crude papain concentration (0,02%; 0,04%; 0,06% and 0,08%) and incubation temperature (room temperature, 40 °C and 50 °C), each combination is repeated twice. The results of this research show that the optimum crude papain concentration is 0,06% and incubation temperature is 40°C. In this condition, the yield of VCO is 49,07%, water content of 0,25 %, saponification number of 258,67 mg KOH/gram, free fatty acid content of 0,38%, iodine value of 8,36 mg/gram, peroxide value of 0,70 meq/kg, lightness (L) of 0,2; a* of 0,3 and b* of 2,0.Key word: VCO, crude papain, incubation temperature, enzymatic method